Analisis Metode Pembelajaran Tahfidz Al-Qur’an Madrasah Aliyah Al-Muayyad Mangkuyudan Surakarta - Nasoha, Ahmad Muhammad Mustain; Khoironi, Arbangin Ardin (Fahima, 2024)
This research is field research, so it is a type of qualitative research with a qualitative descriptive approach, presenting research results in the form of words and sentences. The subjects of this research were recitation teachers and several students of Madrasah Aliyah Al-Muayyad Mangkuyudan in Surakarta. The data collection techniques used in this research are observation, interviews and documentation. Data analysis techniques are based on data reduction, presentation and drawing conclusions. To ensure the accuracy of the research, it was carried out using source triangulation. Based on the research results, in tahfidz learning at Madrasah Aliyah Al-Muayyad Surakarta, 6 tahfidz learning methods were found to be used (1) Tahsin method used by students reading verses from the Koran. want to memorize in front of the teacher and the teacher listens to them, (2) Binadzor method is carried out by the teacher who first reads the verses of the Qur'an then the students, (3) Bandongan method, where students are asked to read the memorized verses repeatedly and then memorize it. (4) The entrustment/talaqqi method is a method where students entrust new memorization to the ustad. (5) The Muroja'ah (repetition) method is carried out by students repeating memorized verses of the Koran under the guidance of the teacher. And the obstacles to implementing the Tahfidz method in learning the Koran at Madrasah Aliyah Al-Muayyad Surakarta are the lack of student attention during learning, an unsupportive learning atmosphere and poor time management. (6) The Sorogan method is a learning method where students read directly in front of the teacher and the teacher listens.